Genetic Characterization of Oncorhynchus mykiss Prior to Dam Removal with Implications for Recolonization of the Elwha River Watershed, Washington. Issue 1 (2nd January 2017) - Winans, Gary A.; Baker, Jon; McHenry, Mike; Ward, Larry; Myers, Jim
Abstract: For more than 100 years, two dams blocked upstream migration of steelhead Oncorhynchus mykiss (anadromous Rainbow Trout) on the Elwha River, Washington. Prior to the removal of both dams (completed in 2015), 30 spatiotemporal collections of resident Rainbow Trout, steelhead, hatchery steelhead, and hatchery-derived Rainbow Trout (1, 949 individuals) were made from 17 sites in the river, and the pattern of genetic diversity and connectivity were evaluated using 13 microsatellite loci. Wild-origin steelhead spawned below the downstream dam and were genetically distinguishable from upriver (above dam) resident Rainbow Trout ( F ST = 0.034), and the resident Rainbow Trout segregated into two distinct groups ( F ST = 0.056). Nonnative-origin hatchery steelhead varied from the indigenous steelhead ( F ST = 0.029), and the hatchery trout differed from the resident trout ( F ST = 0.163). Collections of resident Rainbow Trout from the upper portion of the basin were distinguished by lower estimates of genetic variability ( He, A R, and A/L) and effective population size compared with resident Rainbow Trout in the middle reaches of the Elwha River. The break between the two trout groups coincided with Rica Canyon, 8 river kilometers upstream from the Glines Canyon Dam (the upstream dam), suggesting that the upper and middle trout groups represent historic O. mykiss groups separated by flow conditions in the canyon prior to dam construction. Anticipating the potential for genetic exchange between steelhead and resident Rainbow Trout following dam removal, we evaluated the ability of the microsatellite baseline to distinguish F1 crosses between the life history groups with computer simulations. These results demonstrate how a genetic baseline can be used as a conservation management tool to measure potential genetic introgression among resident populations and recolonizing anadromous populations. Received June 17, 2016; accepted October 10, 2016